2006
DOI: 10.1590/s0004-27492006000300011
|View full text |Cite
|
Sign up to set email alerts
|

Uso de C3F8 no descolamento da membrana de Descemet pós-facectomia

Abstract: Descritores: Extração de catarata/efeitos adversos; Membrana de Descemet; Fluorocarbonetos /administração & dosagem; Edema da córnea/quimioterapia; Injeções INTRODUÇÃO A membrana de Descemet é uma lâmina basal de cerca de 10 µm de espessura que reveste a porção posterior do estroma e o separa do endoté-lio, responsável por sua secreção. Encontra-se frouxamente aderida ao estroma, é homogênea, altamente refrátil, flexível e elástica (apesar de não ter fibras elásticas). Identificam-se duas zonas distintas: ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Our results are comparable to previous studies in terms of DM attachment, visual acuity improvement and resolution of corneal edema. [ 11 ] However, Lucena et al[ 12 ] and Shah et al[ 13 ] have reported success rates of 100%. This difference may be attributed to their small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are comparable to previous studies in terms of DM attachment, visual acuity improvement and resolution of corneal edema. [ 11 ] However, Lucena et al[ 12 ] and Shah et al[ 13 ] have reported success rates of 100%. This difference may be attributed to their small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Não é incomum em cirurgia de catarata, e a incidência é relatada como 0,5 e 2,6% em cirurgia extracapsular e facoemulsificação, respectivamente (17) . Muitas abordagens têm sido relatadas como observação (18) , injeção de gás C3F8 (19,20) ou SF6 (8,20,21) na câmara anterior, injeção de viscoelástico (22) , suturas transcorneanas (23) e transplante de córnea. Descolamento da membrana de Descemet pode ser classificado em planar, quando a separação do estroma é de menos de 1mm; e não-planar, quando a separação é maior que 1mm.…”
Section: Discussionunclassified
“…Indeed, the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) was created to provide classification criteria for the condition that are universally accepted and validated. A diagnosis of MP by the RDC/TMD requires pain to be reported by the subject in response to palpation of three or more sites of the masticatory muscles (De Lucena 2006;Dworkin 1992;Manfredini 2006). Studies of prevalence show di erent results between Americans, Europeans and Asian populations for MP; these studies indicate that MP can occur in 21% to 93% of patients who complain of regional pain.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%